Effects of Vitamin B12 and E on Lipid Profile of Male Wistar Albino Rats Infected with Trypanosomabrucei Infection - Adegoke, Adebayo Olugbenga; Opuda, Ibitoroko Maureen George; Ekweozoh, Ifunaya B (The International Journal of Biotechnology, 2021)
This study was carried out to determine the effect of vitamin B12 and E on the lipid profile of male Wistar albino rats infected with Trypanosomabruceibrucei. 72 male Wistar albino rats were divided into Control, Trypanosome infected, Diamenazene treated, vitamin E, vitamin B12 and various combinations of vitamin B12 and vitamin E. The lipid profile indicators like Triglycerides, Total cholesterol, High Density Lipoprotein and Low Density Lipoprotein were determined using enzymatic methods while Low Density Lipoprotein was determined using Friedewald formula. The data was subjected to statistical analysis using Statistical Package for Social Science (SPSS) version 20. There was a significant decrease (p<0.05) in the Triglycerides (mg/dl), Cholesterol (mg/dl), HDL (mg/dl) and LDL (mg/dl) in trypanosome infected group (52.93±2.76, 51.88±2.20, 37.31±0.81 and 28.85±1.78) and diamenazene treated group (77.55±2.42, 56.18±0.89, 35.26±1.00 and 38.38±0.86) respectively when compared to the respective control concentrations (99.03±6.66, 64.83±2.41, 39.87±0.27 and 38.03±2.81).Vitamin B12 (68.08±5.25, 59.44±2.40, 36.61±0.30 and 38.51±2.89), Vitamin E (68.45 + 3.67, 75.19 + 5.27, 39.91 + 1.47 and 45.42 + 3.74) and Vitamin B12 and E combination (73.17 + 1.94, 79.14+ 2.56, 40.57 + 0.97 and 58.96 + 2.25) showed a significant increase (p<0.05) in the mean concentrations of Triglycerides (mg/dl), Cholesterol (mg/dl), HDL (mg/dl) and a significant increase in LDL (mg/dl) respectively when compared to the trypanosome infected group (52.93±2.76, 51.88±2.20, 37.31±0.81 and 28.85±1.78).The result suggested that oral administration of vitamin B12 and E reversed the changes induced by Trypanosoma brucei brucei infection in Triglycerides, Cholesterol, High Density Lipoprotein and Low Density Lipoprotein.